Catch-22 - Joseph Heller (New York Simon & Schuester, 1961)
"Catch-22," Joseph Heller's classic tale of the loss of faith amid the rise of bureaucratic power, takes place in World War II-era Italy. The Bombadier Yossarian is repeatedly required to increase the number of missions he must fly, even after it becomes clear that the Allies have won. To be taken off these essentially useless missions, a fighter has to be proven insane. According to a rule known as "Catch-22", a man is considered insane if he willingly flies dangerous combat missions, but if he asks to be taken off them that makes him sane, and therefore ineligible to be excused from flying.
Keywords: Fiction; War novel; Classics